Enhancement of spin Hall conductivity in W-Ta alloy - Kim, Jun-Young; Han, Dong-Soo; Vafaee, Mehran; Jaiswal, Samridh; Lee, Kyujoon; Jakob, Gerhard; Klaeui, Mathias (American Institute of Physics, 2020)
Generating pure spin currents via the spin Hall effect in heavy metals has been an active topic of research in the last decade. In order to reduce the energy required to efficiently switch neighboring ferromagnetic layers for applications, one should not only increase the charge-to-spin conversion efficiency but also decrease the longitudinal resistivity of the heavy metal. In this work, we investigate the spin Hall conductivity in W1-xTax/CoFeB/MgO (x = 0–0.2) using spin torque ferromagnetic resonance measurements. Alloying W with Ta leads to a factor of two change in both the damping-like effective spin Hall angle (from −0.15 to −0.3) and longitudinal resistivity (60–120 μΩ cm). At a 11% Ta concentration, a remarkably high spin Hall angle value of –0.3 is achieved with a low longitudinal resistivity of 100 μΩ cm, which could lead to a very low power consumption for this W-based alloy. This work demonstrates that sputter-deposited W–Ta alloys could be a promising material for power-efficient spin current generation.